Investigating healthcare waste management practices among healthcare workers at Samfya District Hospital of Luapula Province - Kalele, Jane C.; Sikazwe, Tresford; Zambwe, Mowa; Mwansa, Pamela (International Journal Of Community Medicine And Public Health, 2026)
Background: Healthcare waste management is a critical component of infection prevention and control within health facilities, however, it still remains a global public health challenge. The purpose of this paper was to assess the healthcare waste management practices among health workers at Samfya District Hospital. Methods: A descriptive cross-sectional study design and quantitative approach was employed. Simple random sampling was used, 65 healthcare workers participated in the study. Data was collected through structured questionnaire and analyzed using STATA version 14.2. Descriptive statistics were used to summarize socio-demographic characteristics and Healthcare waste management practices, while Fishers exact and chi square tests were applied to determine associations between variables. At 95% confidence Interval, a p value <0.05 was considered statistically significant. Results: The study findings revealed that healthcare waste management practices were significantly associated with the presence of properly labelled waste bins (p<0.05, 95% CI), indicating that the availability and proper labelling of bins greatly influenced correct waste segregation and disposal. Furthermore, the profession of healthcare workers showed a statistically significant relationship with healthcare waste management practices (p<0.05, 95% CI), suggesting that knowledge and adherence to waste management protocols varied across professional categories. Conclusions: The study concluded that while awareness of healthcare waste management practices among healthcare workers was high, actual compliance was influenced by structural factors such as the availability of properly labelled bins and professional background.